Spurious point-of-care lactate elevation in ethylene glycol intoxication: rediscovering a clinical pearl. Issue 2 (10th February 2021) - Poirier-Blanchette, Laurence; Simard, Camille; Schwartz, Blair Carl
Abstract : A 76-year-old man was found unresponsive and brought to the emergency department. Initial workup showed profound lactic acidosis on a point-of-care arterial blood gas, without clinical signs of hypoperfusion. Investigations for types A and B lactic acidosis revealed no unifying diagnosis to explain both his altered mental status and profound lactic acidosis. A toxicology workup revealed an increased osmolar gap and an elevated ethylene glycol level. The lactic acidosis and his mental status completely normalised within 8 hours of renal replacement therapy initiation and fomepizole administration. Ethylene glycol metabolites have similar molecular structure with L-lactate. Some blood gas analysers are unable to differentiate them, resulting in an artefactual lactate elevation. Our case highlights the importance of recognising a falsely elevated lactate, which should raise clinical suspicion of ethylene glycol poisoning, as the treatment is time-sensitive to prevent complications and mortality.